Optimalisasi Kader dalam Peningkatan Kualitas Kesehatan Lansia di Candirejo Kecamatan Ungaran Barat Kabupaten Semarang - Minardo, Joyo; Musta'in, Mukhammad; Sugiarto, Heri; Eko Nur Hermansyah; Olif Rina Susanti5 (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Elderly people are very susceptible to health problems due to decreased body function. Complaints of illness experienced by the elderly include respiratory tract disorders, headaches, hypertension, diabetes mellitus, and other degenerative diseases. Health protection for the elderly needs to be considered so that the elderly carry out healthy physical and mental life management. The health of the elderly is facilitated by the Elderly Posyandu program which aims to improve the quality of life of the elderly. Elderly Posyandu is organized by health cadres, who are volunteers recruited from the community. Cadres are not professional health workers, but the role of cadres can help health workers to empower the community. Increasing the knowledge and skills of cadres is very important to support the health of the elderly towards healthy and happy elderly people. Increasing the capacity of cadres is carried out by increasing knowledge about degenerative diseases, and basic examinations. The purpose of this activity is to provide cadres with knowledge about degenerative diseases and how to measure blood pressure as a basic health examination. The method used is to provide health education accompanied by training in blood pressure examinations. The target of this activity is elderly Posyandu cadres. The stages carried out include providing material about degenerative diseases followed by a demonstration of blood pressure measurement. At the evaluation stage, there was an increase in the knowledge and skills of cadres in measuring blood pressure. The results of this activity were that all cadres had good knowledge of 60.71% and very good knowledge of 17.8%, the rest had sufficient knowledge of 21.42%   ABSTRAK Lansia sangat rentan mengalami gangguan kesehatan karena penurunan fungsi tubuh.. Keluhan sakit yang dialami lansia berupa gangguan  saluran pernapasan, sakit kepala, hipertensi, diabetes mellitus, dan gangguan  penyakit degenerative lainnya.  Proteksi kesehatan terhadap lansia perlu diperhatiakan agar lansia  melakukan manajemen hidup sehat jasmani dan rohani. Kesehatan para lansia difasilitasi dengan  program Posyandu Lansia yang bertujuan untuk meningkatkan kualitas hidup lansia. Posyandu lansia diselenggarakan oleh kader kesehatan.yang  merupakan tenaga sukarela yang direkrut dari masyarakat.. Kader bukanlah petugas kesehatan yang profesional, namun peranan kader dapat membantu tenaga kesehatan untuk memperdayakan masyarakat. Peningkatan pengetahuan dan keterampilan kader sangat penting untuk menunjang kesehatan lansia menuju lansia sehat dan bahagia. Peningkatan kapasitas kader dilakukan dengan peningkatan pengetahuan tentang penyakit degeneratif, dan pemeriksaan dasar.. Tujuan dari kegiatan ini adalah untuk memberikan  pengetahuan kader tentang penyakit degenerative dan  cara  pengukuran tekanan darah sebagai pemeriksaan kesehatan dasar.. Metode yang digunakan adalah memberikan penyuluhan kesehatan disertai melatih  pemeriksaan tekanan darah.  Sasaran pada kegiatan ini adalah kader posyandu. lansia  Tahapan yang dilakukan meliputi pemberian materi tentang penyakit degeneratif dilanjutkan demonstrasi pengukuran tekanan darah. Pada tahap evaluasi  terjadi peningkatan pengetahuan dan keterampilan kader dalam mengukur tekanan darah Hasil dari kegiatan ini adalah seluruh kader dengan pengetahuan baik 60,71 % dan pengetahuan baik sekali 17,8 % sisanya dengan pengetahuan cukup 21,42%.